A systematic review and meta-analysis of 30-day readmission rates following burns - Tapking, Christian; Hundeshagen, Gabriel (Burns, 2020)
Introduction - Unplanned hospital readmissions in surgical areas account for high costs and have become an area of focus for health care providers and insurance companies. The aim of this systematic review is to identify the rate and common reasons for unplanned 30-day readmission following burns. - Methods - This study was performed following the PRISMA guidelines. Pubmed, Web of Science and CENTRAL databases were searched for publications without date or language restrictions. Extracted outcomes included 30-day readmission rate and reasons for readmission. Pooled 30-day readmission rate was estimated from weighted individual study estimates using random-effect models. Pooled estimates for risk factors are reported as odds ratios (ORs) and 95% confidence intervals (CIs). - Results - A total of eight studies were included into qualitative analysis and six (four adults, two children) into quantitative analysis. The overall readmission rate was 7.4% (95% CI 4.1-10.7) in adults and 2.7% (95% CI 2.2-3.2) in children. Based on two studies in 112,312 adult burn patients, burn size greater than 20% total body surface area (TBSA) was not a significant predictor of readmission rate (OR 1.75, 95% CI 0.64-4.75; NS). The most common reasons were infection/sepsis, wound healing complications, and pain in both adults and children. - Discussion - Unplanned readmissions following burns are generally low and appear more common in adults than in pediatric patients. However, only few studies are reporting on 30-day readmission rates following burns. Evidence is limited to support a significant association between greater burn size and higher readmission rates. Since cost effectiveness and utilized hospital capacity are becoming an area of focus for improvement in health care, future studies should assess the risk factors of unplanned readmission following burns. Follow-up assessments and outpatient resources, even if not underlined by this data, could reduce readmission rates. - Systematic review registration - PROSPERO: CRD42019117649.